Replace of the EPOST glyphosate with pre herbicides and application of different LPOST glyphosate rates for weed control in established vineyard - Zvonko PACANOSKI; Krum BOŠKOV; Arben Beni MEHMETI (Acta Agriculturae Slovenica, 2020)
Two-year field trials were conducted at two winegrowing districts (Kavadarci and Skopje in 2016 and 2017) to evaluate wheather oxyfluorfen, pendimethalin and flazasulfuron can replace early post-emergence (EPOST) application of glyphosate in established vineyard until its application in early summer period. The weed vegetation in vineyards in both years was consisted mainly of Chenopodium album L., Setaria viridis (L). Beauv., Papaver rhoeas L., Xanthium strumarium L., Lolium multiflorum Lam., Sorghum halepense (L.) Pers. and Cynodon dactylon (L.) Pers. Pendimethalin, oxyfluorfen and flazasulfuron efficiently reduced predominant annual weeds and S. halepense seedlings in 2017, but not in 2016. PRE herbicides, regardless year, had no significant effect on C. dactylon. Opposite, the efficacy of EPOST applied glyphosate was significantly lower in 2017 compared to 2016. LPOST glyphosate applied at 2.0 l ha-1 provided at least 94 % control of dominant annual broadleaf and grass weeds. LPOST application of glyphosate at 2.0 l ha-1 and glyphosate at 2.0 and 4.0 l ha-1 resulted in unsatisfactory weed control of predominant perennial S. halepense, and C. dactylon, respectively. LPOST glyphosate applied at 4.0 l ha-1 provided control of S. halepense by 84 % or more. LPOST glyphosate applied at 8.0 l ha-1 reduced the amount of S. halepense and C. dactylon at least 97 %. Grapevine yield of both varieties was not lower in all herbicide treatments in 2016 compared with 2017. However, yield in the PRE herbicide treatments fb 2.0 and 4.0 l ha-1 glyphosate was collectively 15-19 % and 17-19 % lower compare to PRE herbicide treatments fb 8.0 l ha-1 glyphosate and standard two applications of glyphosate, respectively for both years and districts. No impacts to grapevine growth were observed from PRE herbicide treatments at either district